Analisis Kebocoran Exhaust Valve Mesin Induk Silinder Nomor 4 dan 5 Di MV Natascha Menggunakan Event Tree dan Fishbone Analysis - Robbi, Shofa Dai; Sukarto, Ainur Raihan Nafi; Gupron, Akhmad Kasan; Kristiyono, Antonius Edy; Imanto, Frenki (Jurnal Informasi, Sains dan Teknologi, 2025)
Ships as the main mode of transportation that has a strategic role in trade transportation, the trade supply chain really needs proper operations. The operational of the ship is greatly influenced by the performance of the main engine. One of the critical components of the main engine is the exhaust valve which functions to regulate the release of exhaust gas from the combustion chamber to the exhaust manifold. The research is qualitative, collecting data through observation, documentation, and interviews. The event tree analysis (ETA) method is implemented the sequence of impacts produced by exhaust valve, such as high working temperatures, low engine performance, and standard functions described in the manual book so that leaks can be identified. So, From this analysis, the impacts that are traced sequentially to the performance of the exhaust valve itself can also be found. In addition, a fishbone diagram is used to describe the factors that cause leaks, including human error, managerial deficiencies, neglected inspections, and errors in maintenance techniques. Thus, the right handling can be found to overcome exhaust valve leaks, such as repairs required while the engine is stopped, repeated spare part submissions from ship management, conducting spindle thickness inspections, and improving maintenance techniques as specified in the engine manual book. Proper and effective preventive and handling actions based on the root causes outlined are essential to ensure proper operation of the machine.